Expressed emotion in couples facing breast cancer in women is associated with psychological distress in the first year after surgery. (May 2020) - Favez, Nicolas; Cairo Notari, Sarah; Antonini, Tania; Charvoz, Linda
The aim of this study was to assess the links between partners' and women's expressed emotion with the distress of one another during the first year after surgery for breast cancer in women. The design was longitudinal. A sample of 61 couples participated in the study at 2 weeks, 3 months, and 12 months after the surgery. Expressed emotion was assessed with the Five-Minute Speech Sample. Psychological distress was assessed with a self-reported questionnaire. Mixed-model analyses showed that partners' expressed emotion is associated with heightened psychological distress in women during the first year after surgery, even after medical data were controlled for.